2021
DOI: 10.3390/s21051655
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Mapping of Shear Wave Velocity in Human Tendon: A Proof of Concept Study

Abstract: Ultrasound-based shear wave elastography (SWE) provides the means to quantify tissue mechanical properties in vivo and has proven valuable in detecting degenerative processes in tendons. Its current mode of use is for two-dimensional rendering measurements, which are highly position-dependent. We therefore propose an approach to create a volumetric reconstruction of the mechano-acoustic properties of a structure of interest based on optically tracking the ultrasound probe during free-hand measurement sweeps. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…US assessments and data processing were performed exactly as described in our validation study, which revealed good interoperator reliability (ICC of 0.736) and very good interday reliability (ICC of 0.904) ( Götschi et al, 2021 ). One assessment was performed for each tendon by an experienced examiner; in total, 4 examiners were involved.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…US assessments and data processing were performed exactly as described in our validation study, which revealed good interoperator reliability (ICC of 0.736) and very good interday reliability (ICC of 0.904) ( Götschi et al, 2021 ). One assessment was performed for each tendon by an experienced examiner; in total, 4 examiners were involved.…”
Section: Methodsmentioning
confidence: 99%
“…The tendon was then segmented in the US B-mode volume, and the SWE volume was masked accordingly (3D slicer, version 4.10.2, ( Kikinis et al, 2014 ). To allow analysis of distinct PT regions, the masked SWE reconstruction was divided into three regions with two cuts positioned at a distance of 10 mm from the proximal and distal insertion ( Figure 1B ), analogous to the approach described in our validation study ( Götschi et al, 2021 ). Briefly, the area of interest was identified using landmarks placed during manual segmentation of the volume.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As regenerative stem cell therapies have great therapeutic potential, it is still an active field of research, if such approaches in mechanically exposed tissues such as joints or the periodontium benefit from concomitant mechanical stimulation of the transplanted cells. The so-called "loading history" of the cells might, therefore, play an important role in regenerative stem cell therapies and underscore the pivotal role of MT [365][366][367]. To study these potential influences, Kojima and co-workers presented a micropatterned, polymer-based micropillar research platform that enables the study of FAK and YAP activity in response to mechanical loading.…”
Section: May the Force Be With You: Mt And Its Implications For Periodontal Regenerationmentioning
confidence: 99%